A Cross‐National Examination of Differences in Classification of Lifetime Alcohol Use Disorder Between DSM‐IV and DSM‐5: Findings from the World Mental Health Survey. (18th July 2016) - Slade, Tim; Chiu, Wai‐Tat; Glantz, Meyer; Kessler, Ronald C.; Lago, Luise; Sampson, Nancy; Al‐Hamzawi, Ali; Florescu, Silvia; Moskalewicz, Jacek; Murphy, Sam; Navarro‐Mateu, Fernando; Torres de Galvis, Yolanda; et al.
Abstract : Background: The current study sought to examine the diagnostic overlap in DSM‐IV and DSM‐5 alcohol use disorder (AUD) and determine the clinical correlates of changing diagnostic status across the 2 classification systems. Methods: DSM‐IV and DSM‐5 definitions of AUD were compared using cross‐national community survey data in 9 low‐, middle‐, and high‐income countries. Participants were 31, 367 respondents to surveys in the World Health Organization's World Mental Health Survey Initiative. The Composite International Diagnostic Interview, version 3.0, was used to derive DSM‐IV and DSM‐5 lifetime diagnoses of AUD. Clinical characteristics, also assessed in the surveys, included lifetime DSM‐IV anxiety; mood and drug use disorders; lifetime suicidal ideation, plan, and attempt; general functional impairment; and psychological distress. Results: Compared with DSM‐IV AUD (12.3%, SE = 0.3%), the DSM‐5 definition yielded slightly lower prevalence estimates (10.8%, SE = 0.2%). Almost one‐third ( n = 802) of all DSM‐IV abuse cases switched to subthreshold according to DSM‐5 and one‐quarter ( n = 467) of all DSM‐IV diagnostic orphans switched to mild AUD according to DSM‐5. New cases of DSM‐5 AUD were largely similar to those who maintained their AUD across both classifications. Similarly, new DSM‐5 non cases were similar to those who were subthreshold across both classifications. The exception to this was with regard to the prevalence of any lifetime drug use disorder. Conclusions: In this large cross‐national community sample, the prevalence of DSM‐5 lifetime AUD was only slightly lower than the prevalence of DSM‐IV lifetime AUD. Nonetheless, there was considerable diagnostic switching, with a large number of people inconsistently identified across the 2 DSM classifications. Abstract : Compared with DSM‐IV AUD (12.3%, SE = 0.3%), the DSM‐5 definition yielded slightly lower prevalence estimates (10.8%, SE = 0.2%). Diagnostic switching was common with almost one‐third of all DSM‐IV abuse cases switching to subthreshold in DSM‐5 and one‐quarter of all DSM‐IV diagnostic orphans switching to mild DSM‐5 AUD. Despite this, new cases of DSM‐5 AUD were largely similar to those who maintained their AUD across both classifications. Similarly, new DSM‐5 non ‐cases were similar to those who were subthreshold across both classifications.